Comprehensive analysis of the Co-structures of dipeptidyl peptidase IV and its inhibitor. (December 2016) - Nojima, Hiroyuki; Kanou, Kazuhiko; Terashi, Genki; Takeda-Shitaka, Mayuko; Inoue, Gaku; Atsuda, Koichiro; Itoh, Chihiro; Iguchi, Chie; Matsubara, Hajime
Abstract Background We comprehensively analyzed X-ray cocrystal structures of dipeptidyl peptidase IV (DPP-4) and its inhibitor to clarify whether DPP-4 alters its general or partial structure according to the inhibitor used and whether DPP-4 has a common rule for inhibitor binding. Results All the main and side chains in the inhibitor binding area were minimally altered, except for a few side chains, despite binding to inhibitors of various shapes. Some residues (Arg125, Glu205, Glu206, Tyr662 and Asn710) in the area had binding modes to fix a specific atom of inhibitor to a particular spatial position in DPP-4. We found two specific water molecules that were common to 92 DPP-4 structures. The two water molecules were close to many inhibitors, and seemed to play two roles: maintaining the orientation of the Glu205 and Glu206 side chains through a network via the water molecules, and arranging the inhibitor appropriately at the S2 subsite. Conclusions Our study based on high-quality resources may provide a necessary minimum consensus to help in the discovery of a novel DPP-4 inhibitor that is commercially useful.